Activity of Red Propolis in the control of bacteria in the oral cavity - Silva, Daniela Caroline Barbosa da (2021)
Natural-source products are being studied to preserve human health, including to prevent oral diseases, because industrialized drugs can cause bacterial resistance and adverse effects. Red propolis, a resinous and complex substance, of natural origin produced by bees, has therapeutic properties such as antimicrobial and anti-inflammatory activity. The objective of this work was to verify the antibacterial effect of red propolis in the control of bacteria in the oral cavity and the specific objectives were to compare the effect of propolis with the effect of chlorhexidine and determine in which bacterial strains propolis was more effective. Strains of Escherichia coli (ATCC-25922), Enterococcus faecalis (ATCC-29212) and Staphylococcus aureus (ATCC-25923) were used. The antimicrobial activity of propolis was determined by the agar diffusion method with the well technique. The wells were filled with 40 µL of 0.12% chlorhexidine solutions (positive control), red propolis in concentrations of 12%, 6%, 3%, 1.2%, 0.12%, 0.012% and distilled water (negative control). Tests were performed in triplicate and statistical analysis was performed using Student's t test. Data were organized into tables and graphs to demonstrate the results obtained. Values ​​of p <0.05 were considered significant. It was observed that propolis in general showed similar effectiveness to chlorhexidine in Gram-positive bacteria. It can be concluded that red propolis in its varied concentrations had antimicrobial effects. Its effectiveness was as good as that of chlorhexidine in Gram-positive bacteria and in Gram-negative bacteria there was no inhibitory effect.